Impact of pre‐ and post‐procedural anemia on the incidence of acute kidney injury and 1‐year mortality in patients undergoing transcatheter aortic valve implantation (from the French Aortic National CoreValve and Edwards 2 [FRANCE 2] Registry). Issue 7 (3rd February 2015) - Arai, Takahide; Morice, Marie‐Claude; O'Connor, Stephen A.; Yamamoto, Masanori; Eltchaninoff, Hélène; Leguerrier, Alain; Leprince, Pascal; Laskar, Marc; Iung, Bernard; Fajadet, Jean; Prat, Alain; Lièvre, Michel; et al.
<x xml:space="preserve">Abstract</x> Objectives The relationship between anemia, renal insufficiency, and the outcomes of TAVI patients has not been thoroughly studied. We aimed to evaluate the influence of pre‐ and post‐procedural anemia on the incidence of renal insufficiency, especially AKI, and on the outcomes of TAVI. Methods Data from the French national TAVI registry were collected in 3, 472 patients who underwent TAVI between January 2010 and December 2012. Of these 2, 137 were in the no/mild anemia group, 748 were in the moderate anemia group, and 587 were in the severe anemia group before TAVI. Furthermore, we divided the 3, 472 patients into three groups according to post‐procedural anemia, measured as post‐procedural hemoglobin (Hb) drop: <2 g/dl (n = 1, 633, group 1), 2 to <4 g/dl (n = 1, 458, group 2), and >4 g/dl (n = 381, group 3). Procedure and outcome variables were compared. Results Increased severity of anemia before TAVI was associated with significantly different rates of 1‐year mortality (15%, 19%, and 24%, P < 0.01), with similar differences in the incidence of AKI (5%, 8%, and 10%, P < 0.01). Increased severity of Hb drop was associated with significantly different rates of 1‐year mortality (16%, 18%, and 23%, P < 0.01), and with similar differences in the incidence of AKI (6%, 7%, and 10%, P = 0.04). Both pre‐ and post‐procedural anemia were predictors of the incidence of AKI (OR 1.82, P < 0.01; OR 1.82, P < 0.01, respectively) and 1‐year mortality (HR 1.44, P < 0.01; HR 1.50, P < 0.01, respectively). Conclusions Both pre‐ and post‐procedural anemia were significantly associated AKI and 1‐year mortality. © 2015 Wiley Periodicals, Inc.